Railway noise reduction by the application of CHFC material on the rail - Brigita ALTENBAHER; Darja GOLTNIK; Bojan ROSI (Transport Problems, 2015)
Traffic is the most widespread source of environmental noise. Railway noise has become increasingly common in urban areas in the past few decades. Therefore environmental requirements for railway operations regarding noise are becoming very strict and will become even tighter in future. In the present paper we present actual track-based field test performed on Slovenian Railways. The significant noise reduction (up to 30dBA) was achieved by the application of CHFC material on the rail using CL-E1 top anti noise system.